ANTIBACTERIAL ACTIVITY OF LIANTIBACTERIAL ACTIVITY OF LIANOID AND ARBOREAL SPECIES OF SCHEFFLERA FROM SOUTHERN INDIAANOID AND ARBOREAL SPECIES OF SCHEFFLERA FROM SOUTHERN INDIA - RAGHAVENDRA HEBBAR, DEEPA; NALINI, MONNANDA SOMAIAH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The genus Schefflera belongs to the family Araliaceae. The secondary metabolites of Schefflera include triterpene glycosides, oleanolic acid, and benzyl glycosides with proven biological activities. The objective of this study was to determine the antibacterial potentials of lianoid and arboreal Schefflera spp., from southern India. Methods: Schefflera venulosa, Schefflera stellata, and Schefflera racemosa were collected from the natural forests of Kodagu and Mysore regions of southern Karnataka. The plant parts such as stem bark, leaves, and inflorescence were dried, powdered and known quantity was subjected to Soxhlet extraction based on the solvent polarity. The solvent extracts from each of the species were subjected to preliminary antibacterial screening against five test bacterial strains, namely, Staphylococcus aureus, Streptococcus pyogenes, Bacillus subtilis, Enterobacter aerogenes, and Klebsiella pneumoniae by agar disc diffusion method and the inhibition zones were measured. The minimum inhibitory concentrations (MIC’s) were calculated for the positive extracts and represented. Results: Of the 30 solvent extracts tested, six solvent extracts showed antibacterial activity. The ethanol and ethyl acetate solvent extracts of all three plants showed positive results for antibacterial activity. The zone of inhibition against the bacterial test pathogens ranged from 6.00±0.00 to 15.00±0.00 mm against B. subtilis, E. aerogenes, S. pyogenes, and K. pneumoniae. The highest zones of inhibition were observed for S. racemosa leaf ethanol extract against B. subtilis, E. aerogenes, and S. pyogenes (10.00 mm to 15.00±0.00 mm). The MIC values of the positive extracts were 5.0 mg/ml in the leaf, flower ethanol, and stem bark ethyl acetate extracts of S. venulosa, leaf ethyl acetate and ethanol extracts of S. stellata and the leaf ethanol extract from S. racemosa, respectively. Conclusion: Schefflera spp. from southern India possesses antibacterial potentials, which can be exploited pharmaceutically for potential health benefits against bacterial infections.